2011
DOI: 10.1080/09064702.2011.599859
|View full text |Cite
|
Sign up to set email alerts
|

Water nipples or water bowls for weaned piglets: Effect on water intake, performance, and plasma osmolality

Abstract: Twelve litters were offered nipple drinkers (NIPPLE treatment) as the only source of water after weaning at 32Á35 days of age, and 12 litters were offered water from a water bowl (BOWL treatment). Water usage was measured using water meters and blood samples were taken from four randomly selected piglets from each of eight. The water intake was similar in the two treatments for days 1Á3 and days 4Á7, but significantly higher in the NIPPLE treatment for days 8Á14 (P B0.05). Daily gain was higher (P B0.05) in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 18 publications
2
7
0
Order By: Relevance
“…As predicted, the water quality from the water bowls was clearly inferior to water nipples, which is in accordance with previous findings in pigs [ 10 , 11 ]. Turbidity was higher in the water bowls than what is accepted in human drinking water (< 4 FNU) and also heterotrophy germs at 22°C was higher in the water bowls than recommended (< 100 CFU/ml).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…As predicted, the water quality from the water bowls was clearly inferior to water nipples, which is in accordance with previous findings in pigs [ 10 , 11 ]. Turbidity was higher in the water bowls than what is accepted in human drinking water (< 4 FNU) and also heterotrophy germs at 22°C was higher in the water bowls than recommended (< 100 CFU/ml).…”
Section: Discussionsupporting
confidence: 93%
“…However, both in pigs [ 7 , 8 ] and in sheep [ 9 ] the water intake was higher from nipple drinkers than from water bowls. The water quality seems to be important for the lower intake from water bowls, and both Bøe (1984) and Bøe and Kjelvik (2011) reported a clear reduction in water quality in water bowls [ 9 , 10 ]. Brooks and Carpenter (1989) found that in weaned piglets, the water intake from bowls declined when the water became fouled with feed or feces [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The accumulated average water intake in pre-starter phases I and II, as well as in the total period of nursery, did not differ due to the type of drinker. This suggests that animals had no loss in their development due to lack of water, as this could restrict feed intake (Bøe & Kjelvik, 2011). The results of the present study agree with the values recommended by others (Li et al, 2005;Guerini et al, 2015).…”
Section: Effect Of Drinker Type On Water Intakesupporting
confidence: 92%
“…Although several studies have been conducted to investigate different models of drinkers, water intake (Torrey et al, 2008;Bøe & Kjelvik, 2011) and the behaviour of piglets with different types of environmental enrichment (Van de Weerd, Docking, Day, Breuer, & Edwards, 2006;Maia et al, 2013), there is limited information on water intake with different types of drinkers, as well as on what type of toy improves behavioural activities of piglets.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported that the water intake of pigs using a nipple drinker is comparatively higher than water bowls. Since the water fouled with the feed or faeces, the water intake from the bowl declined when compared to nipple drinkers [10]. Though the water wastage is higher on nipple drinkers than in water bowls, it concluded that pigs prefer to drink from nipple drinkers rather than bowls or troughs [11].…”
Section: Introductionmentioning
confidence: 99%